The Mediating Role of Trust in Generation Z’s Intention to Use Artificial Intelligence-Based Career Preparation Systems - Camelia Kamil; Ratna Roostika (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
Understanding the determinants of Generation Z’s sustained use of Artificial Intelligence-based career assistance is essential, as this cohort increasingly relies on Artificial Intelligence technologies to make high-stakes career decisions. The research examines how information quality shapes performance expectancy and trust, and how performance expectancy, effort expectancy, social influence, facilitating conditions, and trust influence the intention to continue using Artificial Intelligence-based career tools. A quantitative explanatory design with exploratory elements was employed. Data were collected via an online questionnaire distributed to Generation Z individuals who have used Artificial Intelligence for career-related activities, yielding 213 valid respondents. The data were analyzed using PLS-SEM. The findings reveal that information quality significantly enhances both performance expectancy and trust. Performance expectancy, social influence, and facilitating conditions had significant positive effects on the intention to continue using Artificial Intelligence for career preparation. Trust also demonstrated a crucial mediating role in reinforcing continued usage intention. Meanwhile, effort expectancy did not significantly affect intention to continue. Overall, the results highlight the importance of delivering accurate, relevant, and reliable Artificial Intelligence-generated information and building user trust to support sustained Artificial Intelligence adoption among Generation Z.